2017
DOI: 10.3832/ifor2186-010
|View full text |Cite
|
Sign up to set email alerts
|

Understory vegetation dynamics and tree regeneration as affected by deer herbivory in temperate hardwood forests

Abstract: Plant competition and deer browsing are two main factors which limit tree recruitment. We examined natural tree-recruitment processes under continuous-tree-cover management. Changes in plant communities and tree regeneration were monitored over an eight-year period at two different sites in a temperate hardwood forest in the North-East of France. We used paired control plot (unfenced areas, free access to deer) and exclosures (fenced areas, excluding deer) at both sites. Shade-tolerant browsing-tolerant opport… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 30 publications
(29 reference statements)
1
20
0
1
Order By: Relevance
“…Further supporting our hypotheses, we observed an interaction with vegetation control having variable effects in the fenced vs. non-fenced plots. This aligns with results of Owings et al (2017), which showed increased height of planted Castanea dentata [17][18][19][20]. Although vegetation control in the absence of browsing improved seedling development in fenced plots, herbivory was a greater driver of Q. virginiana performance than competition in non-fenced plots.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Further supporting our hypotheses, we observed an interaction with vegetation control having variable effects in the fenced vs. non-fenced plots. This aligns with results of Owings et al (2017), which showed increased height of planted Castanea dentata [17][18][19][20]. Although vegetation control in the absence of browsing improved seedling development in fenced plots, herbivory was a greater driver of Q. virginiana performance than competition in non-fenced plots.…”
Section: Discussionsupporting
confidence: 87%
“…that simultaneous control of browsing and vegetative competition may synergistically improve seedling performance [13][14][15]. While there have been many studies on the individual effects of herbivory and competition, few previous studies have examined the interactive effects, with those that have showing varied results [16][17][18][19][20][21]. Competition between planted seedlings and neighboring vegetation limits the availability of soil nutrients, water, and light, impairing basic plant physiological processes [22].…”
mentioning
confidence: 99%
“…It seems that the height structure of a single tree species or the diversity of tree species per height class or layer of understory vegetation may better indicate browsing pressure than the total abundance of species or the diversity of the entire tree species regeneration. However, little is known about how deer affect the diversity of tree species regeneration when seedlings overgrow height classes (but see Laurent, Mårell, Balandier, Holveck, & Saïd, ; Meier, Stöhr, Walde, & Tasser, ; Schulze et al., ). This information is crucial for understanding the influence of deer on the diversity of the tree species composition of forest stands as well as for assessing the possibility of practicing silvicultural systems that are based on natural regeneration (O'Hara, ).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have been devoted to the research of natural oak regeneration (Dobrowolska, 2008;Götmark & Kiffer, 2014;Levchenko, 2014;Annighöfer et al, 2015;Vizoso-Arribe et al, 2015;Jensen & Löf, 2017;Kopiy et al, 2017;Laurent et al, 2017;Bobiec et al, 2018), in particular in the conditions of the Left-bank Forest-Steppe zone of Ukraine (Tkach et al, 1996;Vedmid et al, 2008;Tkach et al, 2014;Rumiantsev, 2015;Tkach et al, 2015;Chygrynets et al, 2016;Rumiantsev & Lyk'yanets, 2016;Tkach et al, 2017;Didenko & Polyakov, 2018;Rumiantsev et al, 2018a, b). At the same time, this area of research remains relevant due to the need to develop ways to increase the area of oak stands, in particular, by promoting their natural regeneration by sowing.…”
Section: Discussionmentioning
confidence: 99%